Encyclopedia of educational theory and philosophy - Phillips, D. C. (Denis Charles) 1938- (SAGE Reference, 2014)
This reference examines the global landscape of all the key theories and the theorists behind them and presents them in the context needed to understand their strengths and weaknesses. In addition to interpretations of long-established theories, this work offers essays on cutting-edge research and concise, to-the-point definitions of key concepts, ideas, schools, and figures